2017
DOI: 10.1371/journal.pone.0173174
|View full text |Cite
|
Sign up to set email alerts
|

Dietary protein-induced hepatic IGF-1 secretion mediated by PPARγ activation

Abstract: Dietary protein or amino acid (AA) is a crucial nutritional factor to regulate hepatic insulin-like growth factor-1 (IGF-1) expression and secretion. However, the underlying intracellular mechanism by which dietary protein or AA induces IGF-1 expression remains unknown. We compared the IGF-1 gene expression and plasma IGF-1 level of pigs fed with normal crude protein (CP, 20%) and low-protein levels (LP, 14%). RNA sequencing (RNA-seq) was performed to detect transcript expression in the liver in response to di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 53 publications
2
29
0
Order By: Relevance
“…Hepatic transcriptome data (accession number SUB2170304), representing 12, 28 days old, castrated male growing pigs with an initial BW of 9.57 ± 0.64 kg offered 20% CP of diet (CON) or 14% CP of diet for 30 days (the feed intake and final BW were not reported), were downloaded from the NIH Short Read Archive database. This data represented the liver transcriptomic adaption upon moderate PR.…”
Section: Methodsmentioning
confidence: 99%
“…Hepatic transcriptome data (accession number SUB2170304), representing 12, 28 days old, castrated male growing pigs with an initial BW of 9.57 ± 0.64 kg offered 20% CP of diet (CON) or 14% CP of diet for 30 days (the feed intake and final BW were not reported), were downloaded from the NIH Short Read Archive database. This data represented the liver transcriptomic adaption upon moderate PR.…”
Section: Methodsmentioning
confidence: 99%
“…Circulating IGF-1 is controlled by members of the IGF binding protein family (IGFBP-1~6) and acid-labile subunit (ALS). GH, insulin, and nutritional status are responsible for the secretion of IGF-1 [44,45]. The maintenance of hypertrophic phenotype by IGF-1Ea involves also the activation of AMPK pathways, a factor involved in the maintenance of whole-body energy balance and an "energy sensor" controlling glucose and lipid metabolism [46].…”
Section: Introductionmentioning
confidence: 99%
“…Besides JAK2, other upstream regulators of hepatic IGF-1 may mediate its effects, such as FGF21, PPARγ, and components of the hedgehog signaling pathway including Smoothened (66)(67)(68). Furthermore, recent clinical studies have shown ω-3 supplementation and baclofen, a β-p-chlorophenyl derivative of γ-aminobutyric acid (GABA), in increasing plasma IGF-1 concentrations to varying extent (69)(70)(71).…”
Section: Ldlrmentioning
confidence: 99%